Low-Level Laser Therapy versus Resisted Exercise in Hand Function of Patients with Systemic Sclerosis - Samir Abdel-Moneim, Ahmed; Mowafy Emam Mowafy, Zakaria; Abd Allah Hamed, Hamed; Mohmed Ali, Khadra (Journal of Neonatal Surgery, 2025)
Introduction: Systematic sclerosis is connective tissue autoimmune lesion, where nearby 90% suffers` have an apparent hand` functional restrictions. This research designed to estimate the value of low-level laser versus resisted exercise on systemic sclerosis suffers` hand function in line to state the proper management approach for hand function restrictions among systematic sclerosis individuals. Material and methods: Forty participants suffering from systematic sclerosis affecting their hands` function with scleroderma allocated randomly into equal groups; A received 3 sessions per week of low-level laser, also conventional physical program involved stretch, and active mobility training, where B received resisted exercises, also conventional physical program comprising stretching, as well active range of motion exercises. Skin thickness, serum cortisol level, and Hand Grip strength were evaluated pre-, then post- intervention using a Modified Rodnan skin scoring, Serum cortisol laboratory analysis, and hand-held dynamometer (HHD), also pinch gauge, respectively. Results: The groups revealed equivalent remarkable modified Rondon skin thickness, and serum cortisol level reduction, plus highly significant increase in hand grip strength (p < 0.001). Conclusion: Both low-level laser and resisted exercises are equivalent effectively enhance hand grip strength, as well functional capabilities throughout systematic sclerosis management.